2016
DOI: 10.1111/sjpe.12113
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of China's Rise on FDI Competition in East Asia: Crowding‐out or Crowding‐in?

Abstract: This paper investigates the China Effect on FDI competition in East Asia: Does China's FDI crowd out or crowd in FDIs in ASEAN countries? Previous research utilized a gravity equation that has no theoretical foundation for FDI flows. This study applies a theory‐based Knowledge‐Capital Model modified to incorporate preferential market‐openings by FTAs and BITs that directly affect investment and trade costs. Using country‐pair data for China and ASEAN with 34 OECD home countries during 1985–2010, panel analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The inconsistent trends in FDI inflow and the drop in DI rates during the Asian crisis raised debates among the academia and researchers on the issue of whether FDI affects DI positively or otherwise. Most of the studies, such as Haq and Zhu (2016), Sohn (2014), and Tang, Selvanathan, and Selvanathan (2008) found that FDI contributes a positive effect to DI. Thus, this study dug deeper into this issue with the assumption of an inextricable link existing between the two types of investment, namely FDI and DI.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent trends in FDI inflow and the drop in DI rates during the Asian crisis raised debates among the academia and researchers on the issue of whether FDI affects DI positively or otherwise. Most of the studies, such as Haq and Zhu (2016), Sohn (2014), and Tang, Selvanathan, and Selvanathan (2008) found that FDI contributes a positive effect to DI. Thus, this study dug deeper into this issue with the assumption of an inextricable link existing between the two types of investment, namely FDI and DI.…”
Section: Introductionmentioning
confidence: 99%
“…The theory does not put forth any clear prediction regarding the impact of distance on FDI inflows to the host country. Moreover, the variable impacts trade and investment, so the sign of its coefficient is ambiguous (Sohn, 2016). However, prior empirical studies suggest an adverse impact of distance on FDI inflows (Cieslik, 2020; Kristjansdottir, 2010; Nguyen et al, 2019).…”
Section: Hypotheses Of the Studymentioning
confidence: 99%
“…In other words, this variable represents the horizontal motivation of FDI since the motive of horizontal FDI is to further serve the host country's market with its increasing size. Thus, GDP sum is expected to positively associate FDI for its horizontal inflows (Carr et al, 2001;Kristjansdottir, 2010;Sohn, 2016…”
Section: Hypotheses Of the Studymentioning
confidence: 99%
“…A study of FDI by Sohn (2014) applied the Knowledge-Capital model (CMM) where they concluded that FDI inflow of China does not pose a threat to neighbouring ASEAN countries unless they are complementary to each other. Another study done by Ang (2009) investigated the long run relationship between private domestic investment, public investment and FDI in Malaysia during the period of 1960-2003.…”
Section: Literature Reviewmentioning
confidence: 99%